Provider perspectives on a clinical demonstration project to transition patients with stable mental health conditions to primary care. Issue 1 (3rd December 2019) - Fletcher, Terri L; Johnson, Adrienne L; Kim, Bo; Yusuf, Zenab; Benzer, Justin; Smith, Tracey
Abstract: Research to improve access to mental healthcare often focuses on increasing timely referrals from primary care (PC) to specialty mental health (SMH). However, timely and appropriate transitions back to PC are indispensable for increasing access to SMH for new patients. We developed and implemented a formalized process to identify patients eligible for transition from SMH to PC. The FLOW intervention was piloted at a Veterans Health Administration community-based outpatient clinic. Qualitatively examine provider perspectives regarding patient transitions at initiation and termination of the FLOW project. Sixteen mental health providers and three PC staff completed qualitative interviews about the benefits and drawbacks of FLOW at initiation. Ten mental health providers and one PC staff completed interviews at 12-month follow-up. Primary benefits anticipated at initiation were that FLOW would increase access to SMH, provide acknowledgment of veterans' recovery, and differentiate between higher and lower intensity mental health services. SMH providers reported additional perceived benefits at 12-month follow-up, including decreased stress over their caseloads and increased ability to deliver efficient, effective treatment. Anticipated drawbacks at initiation were that veterans would get inconsistent care, PC could not offer the same level of care as SMH, and veterans might view transition as a rejection by their SMH provider. Perceived drawbacks were similar at 12-month follow-up, but there was less frequent endorsement. Findings highlight need for sustained and frequent provider education regarding (i) the appropriate characteristics of individuals eligible for transition and (ii) established procedures to ensure care coordination during and after transition.